2016
DOI: 10.1111/evo.13015
|View full text |Cite
|
Sign up to set email alerts
|

Fertility depression among cheese‐makingPenicillium roquefortistrains suggests degeneration during domestication

Abstract: Genetic differentiation occurs when gene flow is prevented, due to reproductive barriers or asexuality. Investigating the early barriers to gene flow is important for understanding the process of speciation. Here, we therefore investigated reproductive isolation between different genetic clusters of the fungus Penicillium roqueforti, used for maturing blue cheeses, and also occurring as food spoiler or in silage. We investigated premating and postmating fertility between and within three genetic clusters (two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
2
28
0
2
Order By: Relevance
“…There was no particular sampling bias regarding geography either (Table S1). A previous study showed that these bottlenecks, together with clonal multiplication, decreased fertility, with different stages in sexual reproduction affected in the two populations identified here as the Roquefort and non-Roquefort lineages (Ropars et al, 2016b). The non-Roquefort cheese population, despite suffering from a more severe and more recent bottleneck, was found to be used in the production of all types of blue cheese worldwide, including Gorgonzola, Bleu d’Auvergne, Stilton, Cabrales and Fourme d’Ambert.…”
Section: Discussionmentioning
confidence: 67%
“…There was no particular sampling bias regarding geography either (Table S1). A previous study showed that these bottlenecks, together with clonal multiplication, decreased fertility, with different stages in sexual reproduction affected in the two populations identified here as the Roquefort and non-Roquefort lineages (Ropars et al, 2016b). The non-Roquefort cheese population, despite suffering from a more severe and more recent bottleneck, was found to be used in the production of all types of blue cheese worldwide, including Gorgonzola, Bleu d’Auvergne, Stilton, Cabrales and Fourme d’Ambert.…”
Section: Discussionmentioning
confidence: 67%
“…Although the different species within the Mucoromycotina subphylum are expected to produce and accumulate large amount of carotenoids, differences might exist among species [60]. Terpenes play also an important role in flavour production which is an important trait for cheese-ripening fungi that could have been under human-directed selection in species used for cheese making [61]. This study indicated that the main genes involved in terpene biosynthesis were conserved among the analysed Mucor species without any important differences in terms of gene number with the exception of GGPP genes for which the number is lower in the endophytic species as well as in M. griseocyanus and in the M. indicus opportunistic pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the female sterile mutants then released the spores they produced more efficiently, which is considered crucial for the invasion of natural populations by female sterile mutants ( 21 ). In Penicillium roqueforti , fertility also decreases during industrial use and the necessary clonal replication there ( 20 ). A similar phenomenon may have happened for QM6a, but we have isolates from natural environment that are female sterile as well.…”
Section: Discussionmentioning
confidence: 99%
“…Considering sexual development as a tool in industry, it is required that this process work reliably and continuously. However, it was shown for other fungi that asexual cultivation, which is routinely done for inoculum generation, results in the loss of female fertility ( 20 , 21 ). Also, for T. reesei QM6a, it was considered possible that its defect might be a result of repetitive laboratory cultivation ( 12 ).…”
Section: Introductionmentioning
confidence: 99%